Knowledge management strategies for sustaining Lesson Study. Issue 2 (10th December 2019) - Cheng, Eric C.K.
Abstract : Purpose: The purpose of this paper is explore the relative effectiveness of people-based and information technology-based knowledge management (KM) strategies as implemented by principals in Hong Kong schools to facilitate and sustain Lesson Study for teachers' knowledge sharing and internalization. Design/methodology/approach: Data from 184 principals in Hong Kong were collected by a cross-sectional quantitative survey. Confirmatory factor analysis and reliability tests have been used to examine the constructed validity and reliability of the instrument. A structural equation model was applied to confirm the predictive effect of people-based and information technology-based KM strategies on teachers' knowledge sharing and internalization through Lesson Study. Findings: Results show that people-based KM strategy predicts knowledge sharing and internalization by and among teachers. However, while information technology-based knowledge management strategies predict teachers' knowledge sharing, they do not predict how effectively they internalize knowledge. Practical implications: Cultivating communities of practice, professional learning communities and mentoring schemes in schools can nurture a knowledge-sharing culture to facilitate and sustain Lesson Study for teacher learning. Institutionalizing an information technology system can help teachers to retrieve, share and store the school's explicit knowledge. Originality/value: The paper not only suggests school management strategies and practices for school leaders to facilitate and sustain Lesson Study, but also brings a new research dimension, KM, to the research area.